X-ray emission from heavy atomic collisions : couplings of inner shells in superheavy quasimolecules - Verma, Punita; Justus Liebig University Giessen (My University, 2010)
Overcritical electromagnetic fields with a coupling strength of ZUA greater than or equal to 1/alpha (=137, with alpha being the fine structure constant) can be experienced in superheavy quasimolecules (atomic number ZUA = Z1+Z2) formed transiently in close collisions of two very heavy atomic partners (Z1, Z2) at velocities (vion) smaller compared to the orbital velocity of the innermost electrons of concern (ve-). The inner shell processes in these collisions are governed approximately by the adiabaticity parameter (= vion/ve-)2. Beyond ZUA = 137 the normal Dirac equation for a point charge cannot be solved and for ZUA > 160 the innermost electron levels even dive into the negative continuum. Moderately slow (vion<ve-), heavy ions are now available even in the highest charge states (bare, H-like, etc.) at SIS (heavy ion synchrotron at GSI, Darmstadt) due to advanced accelerator technologies. Thus slow, heavy projectiles with prior-to-collision vacancies in the innermost shells can be provided for the study of ion-atom collision processes. The X-ray emission for closed and open projectile K-shell gives access to vacancy transfer in the superheavy quasimolecule. Depending on the target thickness some of the projectile K-vacancies may be destroyed while penetrating solids. The goal of the present investigation is to establish the survival time of projectile high charge states in collisions with thin solid targets at relatively low collision velocities and to investigate the possibility of using solid targets for studying superheavy quasimolecules with open, well-defined inner shell vacancy channels. Experiments have been performed at SIS for a slightly asymmetric (U-Au) and for a near symmetric (Bi-Au) very heavy collision system. Charge state selected Uq+ ion (q ranging from 73 to 92) and Biq+ ion (q ranging from 77 to 82) beams of 69.2 MeV/u from the SIS were incident on thin Au targets (from 18 to 225 microgm/cm2 thick). Incoming projectile charge state (q) as well as target thickness (t) dependences were investigated for both K and L x-ray emission of the collision partners. Charge state distribution of the emerging ions has been measured by a position sensitive CVD-diamond detector after being analyzed by a magnet spectrometer and the x-ray emission by standard Ge and Si solid state detectors. Charge exchange cross sections have been deduced from the target thickness dependence of the charge state distribution. Heavy projectiles provide the possibility to measure shell differential electron capture into higher shells via the characteristic x-ray emission during stabilization as long as there are inner shell vacancies available. From the x-ray emission both total and shell differential capture cross sections have been deduced. These have been compared with measured charge exchange cross sections and with theoretical calculations. Both the values are in consonance. The U and Bi-K x-ray emission cross sections lead to an estimation of the projectile K vacancy lifetime in the bulk of the target. The extrapolation of the Au-K x-ray emission cross section to zero target thickness gives, to some approximation, these values under single collision conditions. Thus the half-survival time of the incoming projectile K vacancy in the target bulk has been estimated to be in the range of 4 to 9x10-16 s for these collision systems. The corresponding thickness in Au foils for half of the projectiles to retain their K vacancies is in the range 150±40 microgm/cm2, several confirmatory tests being performed and all giving comparable results. The couplings between the innermost shells of these superheavy quasimolecules can be probed with these highly charged projectiles and the interaction distances for the inner shell couplings can be estimated. For H-like projectile-ions, the K-vacancies brought in the collision are shared between the projectile and the target Au atoms. For an incoming K vacancy (U91+/Bi82+), the interaction distance for electron capture (10000 to 13000 fm) has been estimated from the increase in projectile-K emission, for K-K vacancy transfer (2000 to 3000 fm) from the increase in the Au-K cross sections and that for L-K coupling (~1000 fm) from the increase in Au-K cross sections for incoming L1/2 vacancies. As the adiabaticity factor for the inner shells of both the systems is smaller than 1, both lie in the quasiadiabatic regime and hence the transfer of inner shell vacancies can be considered within the quasimolecular picture using adiabatic level diagrams. Available advanced SCF-DFS (Self Consistent Field-Dirac Fock Slater) multi electron level diagrams for the two systems were used for interpretation. A comparative study of the two systems has been presented. With the results of the present investigation, the basis for a detailed probe into the inner shells of superheavy quasimolecules is laid opening the way for further experimental investigations at better adiabatic conditions.
Röntgen-Emission in schweren atomaren Stößen : Kopplungen innerer Schalen in superschweren Quasimolekülen
Keywords: ion-atom collisions; superheavy systems; quasimolecules; x-ray emission charge exchange; survival thickness; ddc:530